Reliability and validity of the Neck Disability Index among patients undergoing cervical surgery - Widbom-Kolhanen Sara; Pernaa Katri I.; Saltychev Mikhail (Lippincott Williams & Wilkins, 2022)
To explore the internal consistency and factor structure of the Neck Disability Index (NDI) among patients undergoing surgery on the cervical spine. This was an observational retrospective cohort study among 392 patients undergoing cervical surgery of any kind in a university hospital between 2018 and 2021. The patients responded to repeated surveys preoperatively, and 3, 12 and 24 months postoperatively. The reliability and validity of the NDI were investigated using Cronbach's alpha and factor analysis. The internal consistency of the NDI was found to be good at 0.86. The exploratory factor analysis demonstrated unidimensionality. The correlations between the main factor 'disability' and all the individual items of the NDI were at least moderate. The highest correlations were observed for pain intensity, reading, driving and recreation. The NDI is an internally consistent and unidimensional scale when applied to a population of patients undergoing cervical surgery.